A Semiotic Analysis of the Meaning of Longing in the Lyrics of the Song “Lagu Untukmu” by Raisa - Azmi Nailan Wisam; Khaerudin Imawan (Salus Publica: Journal of Community Service, 2026)
Song lyrics can act as a means of expressing one’s emotions, meanings, and particular symbols. This research intends to explore the concept of longing present in the lyrics of the song “Lagu Untukmu” through the lens of Ferdinand de Saussure’s semiotic theory. Saussure’s semiotic theory emphasizes two elements: the signifier and the signified. This study employs an interpretative qualitative approach and operationalizes Ferdinand de Saussure’s semiotic framework by analyzing the relationship between signifiers and signified meanings in the song lyrics. Data were collected through document analysis of song lyrics and in-depth interviews with selected listeners, which were used to complement the semiotic analysis. The result indicate that the meaning of longing is constructed through a system of linguistic signs representing emotional distance, memory, and maternal attachment. This longing represents not only physical yearning but also emotional yearning for unconditional acceptance, a sense of security, the warmth of the relationship, and memories of the past that have changed due to life transitions. The conclusion of this study is that song lyrics can serve as a medium for conveying messages or feelings experienced by the singer to the listener.